Multiple visible optical Tamm states supported by graphene-coated distributed Bragg reflectors. (30th August 2017) - Zheng, Gaige; Qiu, Menghan; Xian, Fenglin; Chen, Yunyun; Xu, Linhua; Wang, Jicheng
Abstract: A planar graphene-coated multilayer configuration for the excitation of multiple optical Tamm states and significant improvement of the light absorption has been demonstrated. Significantly, unity absorption can be realized in graphene for which the total thickness of the absorbing layer is as small as 1/220 of the incident wavelength. The designed graphene absorber has excellent optical performance for sensing applications, along with the advantage of an all-dielectric form. Additionally, our proposed methodology is applicable to other two-dimensional materials with deep sub-wavelength thicknesses and paves the way for efficient energy-harvesting devices with simple planar structures.